Light Quality Modulates Plant Cold Response and Freezing Tolerance - Kameniarová, Michaela; Černý, Martin; Novák, Jan; Ondrisková, Vladěna; Hrušková, Lenka; Berka, Miroslav; Vankova, Radomira; Brzobohatý, Bretislav (Frontiers in Plant Science, 2022)
The cold acclimation process is regulated by many factors like ambient temperature, day length, light intensity, or hormonal status. Experiments with plants grown under different light-quality conditions indicate that the plant response to cold is also a light-quality-dependent process. Here, the role of light quality in the cold response was studied in one-month-old Arabidopsis thaliana (Col-0) plants exposed for one week to 4 °C at short-day conditions under white (100 and 20 μmol m-2s-1), blue or red (20 μmol m-2s-1) light conditions. An upregulated expression of CBF1, an inhibition of photosynthesis, and an increase in membrane damage showed that blue light enhanced the effect of low temperature. Interestingly, cold-treated plants under blue and red light showed only limited freezing tolerance compared to white light cold-treated plants. Next, the specificity of the light quality signal in cold response was evaluated in Arabidopsis accessions originating from different and contrasting latitudes. In all but one Arabidopsis accessions, blue light increased the effect of cold on photosynthetic parameters and electrolyte leakage. This effect was not found for Ws-0, which lacks functional CRY2 protein, indicating its role in the cold response. Proteomics data confirmed significant differences between red and blue light treated plants at low temperature and showed that the cold response is highly accession specific. In general, blue light increased mainly the cold-stress related proteins and red light induced higher expression of chloroplast-related proteins, which correlated with higher photosynthetic parameters in red light cold-treated plants. Altogether, our data suggest that light modulates two distinct mechanisms during the cold treatment - red light driven cell function maintaining program and blue light activated specific cold response. The importance of mutual complementarity of these mechanisms was demonstrated by significantly higher freezing tolerance of cold-treated plants under white light.